"With a tongue forked in two": Translingual Arab writers in Israel. (April 2014) - Tannenbaum, Michal
Members of the Arab minority in Israel comprise about 20% of the Israeli population and differ from the Jewish majority in their nationality, religion and language. Though legally enjoying equal rights, they suffer discrimination in a variety of areas. Relationships between Jews and Arabs have been conflictual since long before Israel's establishment as an independent state, and to this day are marked by suspicion and at times hostility. For most Arabs who are citizens of Israel, their sense of identity is complex and often described as placing them "between hammer and anvil" due to their unique position within Israeli society, their connectedness to the Palestinian cause and their relationship with the surrounding Arab countries. This identity also involves linguistic aspects: Arabs in Israel speak Arabic as their first language and study in a separate educational system in Arabic. Hebrew, the language of the Jewish majority, is studied as a second language from second grade onwards and matriculation exams in Hebrew are compulsory. Israeli Arabs largely master Hebrew, though many view it as a language of conflict or even of oppression. This paper deals with four Israeli Arab novelists and poets who chose to write in Hebrew, focusing on interfaces of linguistic, sociological, psychological and political aspects and on patterns of language usage in their writings. Their works suggests a new channel for exploring the broader context of Jewish–Arab relationships in Israeli society and contributes new insights on the potential of the linguistic angle to shed light on minority–majority relationships.